Czechoslovak Diplomacy and the Gulag : Deportation of Czechoslovak Citizens to the USSR and the Negotiation for their Repatriation, 1945-1953 - Polišenská, Milada (Central European University Press, 2022)
After the entry of the Red Army into Czechoslovak territory in 1945, Red Army authorities began to arrest and deport Czechoslovak citizens to labor camps in the Soviet Union. The regions most affected were Eastern and South Slovakia and Prague. The Czechoslovak authorities repeatedly requested a halt to the deportations and that the deported Czechoslovaks be returned immediately. It took a long time before these protests generated any response. Czechoslovak Diplomacy and the Gulag focuses on the diplomatic and political aspects of the deportations. The author explains the steps taken by the Czechoslovak Government in the repatriation agenda from 1945 to 1953 and reconstructs the negotiations with the Soviets. The research tries to answer the question of why and how the Russians deported the civilian population from Czechoslovakia which was their allied country already during the war. Key words: 1. World War, 1939-1945-Deportations from Czechoslovakia. 2. Forced labor-Soviet Union-History. 3. Labor camps-Soviet Union-History. 4. Czechs-Soviet Union-History. 5. Slovaks-Soviet Union-History. 6. Czechoslovakia-Foreign relations-Soviet Union. 7. Soviet Union-Foreign relations-Czechoslovakia. 8. Czechoslovakia-Foreign relations-1945-1992. 9. Repatriation-Czechoslovakia-History.